The First Post-War Electoral Campaign in the Modern Statehood of Bosnia and Herzegovina - Denis P. Eremin (Современная Европа)
The article examines the preparation, course and practical results of the first post-war election campaign of 1996 in Bosnia and Herzegovina. The 1995 Dayton Accords, which became the foundation of modern Bosnian-Herzegovinan statehood, represented a compromise imposed from without and it could not resolve the fundamental contradictions of the country's national communities. Consequently, the situation in Bosnia retained a significant conflict potential. Сoncerned international actors, primarily the United States and the EU countries, that directed the process of resolving the crisis in Bosnia, used institutional peace-building as the main method of post-conflict settlement. Therefore, the first post-war election campaign played a key role in building a new political system of BiH, since the process of formation of new authorities depended on its results. The lack of real harmonization of community relations, their mutual bitterness on national and religious grounds predetermined the inability of ethnic parties to reach the necessary compromises independently. This fact, fully represented by the first post-war election campaign, predetermined high involvement of Western countries in the state's domestic political life, the formation of a supranational structure of governance and the transformation of Bosnia into an international protectorate. The research is developed on unintroduced for scientific use materials of the Foreign Policy Archive of the Russian Federation (AVP RF) and based on historical method.